The equal pillars of sustainability - Crowther, David; Seifi, Shahla (Developments in corporate governance and responsibility ;, 2022)
The three pillars of sustainability - Environmental protection, Social sustainability, and Economic sustainability - are well known since the Brunndtland Commission report. However, these pillars are meant to be approached and treated as equal counterparts, yet this rarely happens as individuals, corporations, businesses, and institutions will weight one pillar with more importance than the others. The Equal Pillars of Sustainability works to redress this problem and to look at what action is taken or might be taken to achieve equality. It is investigated whether this equality can be achieved in all circumstances or what alternatives need to be considered. It might be argued that Brundtland was wrong, and these three pillars are not the centrepiece of sustainable development. In this book we consider these views and actions to arrive at a view which will inform debate and guide future action. Developments in Corporate Governance and Responsibility as a series offers the latest research on topical issues by international experts and has practical relevance to business managers. This is the only book series endorsed by the Social Responsibility Research Network.